MENDIALOGKAN DIMENSI KEILMUAN USHUL FIQH - Abu Yasid (LP2M Universitas Ibrahimy, 2015)
As a method of rational thinking, ushul fiqh not purely built on a foundation of logic, but also based on wahyu. The Ulama did not take the rules of usul fiqh as adapted a formal logic, but they adapt and changing into a new logical thinking which covers the whole essence of religious teachings. The colaboration wahyu and logic that makes ushul fiqh survive alot of time, even attracted the attention of the scientific to be continuously assessed. Epistemologically, usul fiqh is a scientific theory that to see work based on the Islamic arguments law. Ushul fiqh not born in empty space, but is present in accordance challenges and legal needs. The science of fiqh ushul built to formulate rules to get an Istinbath hokum according to the change and development of society